Pengembangan booklet sebagai media edukasi pencegahan stunting serta implementasinya terhadap pengetahuan dan sikap calon pengantin - Siti Asiyah; Dini Junita (DAPU Aceh Publishing, 2025)
Stunting is a nutritional problem that is closely related to the development and growth of children caused by poor nutritional status that lasts for a long time. Prevention and handling of stunting can be pursued by increasing knowledge and changing attitudes starting from the time the mother prepares for pregnancy and is still a prospective bride. The purpose of this study was to determine the development of booklets as a medium for stunting prevention education and its implementation on the knowledge and attitudes of prospective brides at the Johan Pahlawan Health Center in West Aceh. The type of research used is Research & Development method, which is a form of development research in the form of media using the ADDIE product development model (Analysis, Design, Development, Implementation, Evaluation) and testing product results on knowledge and attitudes with Pre-Post Test using Paired T test and Wilcoxon test. Paired T test statistics on the knowledge variable obtained a value of p = 0.000 (p < 0.05) and the statistical results of the Wilcoxon test on the attitude variable obtained a value of p = 0.000 (p < 0.05) which means Ho is rejected and Ha is accepted which indicates the influence of booklets as educational media in increasing knowledge and changing the attitude of prospective brides or there is a difference in knowledge and attitude scores before and after being given education through booklet media about stunting prevention.